The Relational Database Dictionary, Extended Edition - Date, C. J. (Apress, 2011)
C.J.Date, one of the creators of the relational database model, and a team lead on the original DB2, created this 900 word dictionary of relational database terms as a handy reference. The reason for the book is that over half the terms are common English, such as “data definition, join, attribute, predicate, index, cube, key, DDS, table…” and when they are defined, even worse, the definitions are imprecise. It is a chore to find their true relational database meaning online. A version of the book with 586 definitions was published by O’Reilly and feedback from that book, along with numerous updates, led to this 900 word book.